The Effect of Double Triangle and Double Square Trainings on Passing Results in Disporasu Football Players Aged 10-11 - Nicodemus Hutagaol; Dewi Endriani (Sports and Coaching Education, Faculty of Sports Science, Universitas Negeri Medan, 2024)
This research aims to determine the effect of double triangle and double square training on passing results in football players aged 10-11 years at Disporasu Football School (FS) in 2022. The research method used is an experimental method, namely to see a change from before treatment and after treatment and then in compare. This research uses a research design, namely one group pretest-posttest design. This research has a population of 18 people from the entire 10-11 year age category in Disporasu FS in 2022, to make it easier in the research the researcher has certain criteria, then the sample is taken using a purposive sample technique, namely a conditional sampling technique, so it can be obtained The sample was 14 people. The time of this research was carried out 18 meetings. The data collection techniques used in this research are tests and measurements. The test instrument used in this research was the football short pass test. The data analysis technique used is the normality test, the results of the pretest data normality test are Lcount 0.1493 and posttest data 0.1472 with Ltable 0.227 with the conclusion that the data is normally distributed, homogeneity test, the data homogeneity test results state that Fcount is 1.21 with Ftable 2 .58, then the conclusion that can be drawn is that the data comes from homogeneous variance and the t test with the help of SPSS 21. The results of the t-test state that there is a value of Tcount=16.60442, then the value of Tcount is compared with the value of Ttable with dk=n-1 (dk=14-1=13) at a significance level of Î¬=0.05, so we get Ttable=2 .16037, so that based on the hypothesis testing criteria it is stated that at Tcount=16.60442 > Ttable=2.16037, so Ho was accepted.